Therapeutic Management of Buxtonella sulcata Infection in a Crossbred Cow - Nath, Mrinal Kumar; Devi, Pallabi; Deka, Abhijit; Hazorika, Mousumi; Das, Arunima; Barman, Utpal; Das, Arup (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
This case report documents the successful therapeutic management of Buxtonella sulcata-associated diarrhoea in a crossbred cow. A lactating crossbred cow with a history of explosive mucoid diarrhoea and progressive loss of appetite was diagnosed by coprological examination and treated accordingly.